Analysis of Efficiency Strategies For Four-Wheeled Fish Transport Facilities At Batulicin Fishing Port, South Kalimantan - Siti A’isyah; Emmy Sri Mahreda; Emmy Lilimantik (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Fish distribution requires efficient transportation facilities because fish are highly perishable commodities and are strongly affected by time, temperature, and logistics costs. This study aimed to analyze the efficiency of four-wheeled fish transport facilities and to formulate efficiency strategies for fish transportation at Batulicin Fishing Port, South Kalimantan. The study used a mixed-methods approach. Load factor analysis was applied to assess vehicle-capacity efficiency, while IFE, EFE, and SWOT analyses were used to formulate management strategies. Data were collected through observation, interviews, questionnaires, and port distribution documents. The results showed that the load factor reached 100%, indicating that four-wheeled fish transport facilities were in the efficient category. The IFE results showed total scores of 3.59 for fishers, 3.41 for agents, and 3.53 for transport drivers. The EFE results showed total scores of 3.65 for fishers, 3.13 for agents, and 3.77 for transport drivers. The priority strategies include strengthening coordination among distribution actors, improving cold chain facilities, adopting digital distribution technology, optimizing routes and loads, conducting regular vehicle maintenance, and providing emergency storage facilities. This study confirms that transport efficiency is determined not only by capacity utilization, but also by facility quality, distribution management, infrastructure support, and the ability of actors to respond to external risks.